The Practices of the Council of Europe and the European Court of Human Rights From a Central European Perspective Regarding Questions on Migration - Fábián, Gyula (Migration and Central Europe: Challenges and Legal Responses, 2024)
Over the past decade, Europe and particularly the European Union annually receive several migrants owing to the failure to respect the principle of the ‘first safe state’ according to public international law, and a lack of effective measures to address the causes of migration. In this context, the Council of Europe, as a classical, non-supranational international cooperation organisation was unable to regulate migration policies, although it aims to protect human rights on the European continent. This was largely owing to the members’ reluctance regarding asylum regulations and the ‘soft law’ initiatives adopted by its institutions. It was not until the migration phenomenon caught the attention of the ECtHR in 1999 that the situation began to change. The ECtHR relies on the ECHR to prevent member states from returning or expelling aliens who have entered their territory illegally, replacing the lack of anchoring of the right of asylum in positive law with the impossibility of removing people who do not fulfil the criteria for refugee status owing to substantive or procedural loopholes. In the absence of a pan-European lex specialis on migration, the ECtHR is forcing a lex generalis to oblige some 600 million Europeans to host several billion people who seek a better future in Europe, often overlooking the principle of ‘safe first country’ for those who are genuinely persecuted within the meaning of the 1951 Geneva Convention relating to the Status of Refugees. This study reviews the powers, instruments, and means available to the Council of Europe in relation to the member states of the Council of Europe with respect to migration, dealing with the problem of the imposition of the ECHR by the ECtHR as lex generalis in the absence of lex specialis, particularly in relation to Eastern and Central European countries. Although they have no colonial past laden with ‘moral debts’ and are not the priority target of migration, they are unjustifiably and sometimes excessively ‘condemned’ by the ECtHR.Keywords: vulnerable group, detention for extradition vs detention for deportation, accountability of member states, Special Representative for Migration and Refugees, rich imagination with soft law results, asylum seeker